Associations of serum lactate and lactate clearance with delirium in the early stage of ICU: a retrospective cohort study of the MIMIC-IV database - Qian, Xiangfeng; Sheng, Yi; Jiang, Yinsheng; Xu, Yong’an (Frontiers in Neurology, 2024)
To investigate the associations of serum lactate level (within and after 24 hours of the intensive care unit (ICU) admission) and lactate clearance rate with delirium, and assess associations of lactate and lactate clearance rate with 30-day mortality in delirium patients.Data in this retrospective cohort study were extracted from the Medical Information Mart for Intensive Care IV (MIMIC-IV) database in 2012-2019.The associations of lactate and lactate clearance rate with delirium were explored through univariable and multivariable logistic regression analyses, whereas the associations of lactate and lactate clearance rate with 30-day mortality in delirium patients were investigated by univariable and multivariable Cox regression analyses.Subgroup analysis of age, gender, sepsis, hypertension, sedative drug, ventilation, antibiotic drug, vasopressors, and the Sequential Organ Failure Assessment (SOFA) score was also performed.The evaluation indexes were odds ratios (ORs), hazard ratios (HRs) and 95% confidence intervals (CIs).Among 7,812 (14.58%) eligible participants, 4,338 (8.19%) had delirium and 1,903 (24.36%) died within 30 days. After adjusting for covariates, patients with lactic acidosis (lactate level >5 mmol/L and PH<7.35) at T0 (within 24 hours of the ICU admission) had higher odds of delirium (OR=1.235, 95%CI: 1.105-1.382).Hyperlactatemia (lactate level 2-5 mmol/L and PH>7.35) at T1 (after 24 hours of the ICU admission) was also associated with higher odds of delirium (OR=1.277, 95%CI:1.126-1.447). Lactate clearance rate >50% was linked to lower odd of delirium Lactate and delirium in the ICU 3 (OR=0.705, 95%CI: 0.613-0.811), and this relationship was also observed in ≥65 years old, female, male, non-sepsis, sepsis, non-hypertension, non-sedative drug use, sedative drug use, ventilation, antibiotic drug use, vasopressors use, and different SOFA score subgroups (all P<0.05). Additionally, hyperlactatemia and lactic acidosis (whether at T0 or T1) may be potential risk factors for 30-day mortality in delirium patients, whereas lactate clearance rate ≥0 had a potential protective effect on 30-day mortality (all P<0.05).Higher serum lactate levels in early stage of the ICU were associated with higher risk of delirium and subsequent mortality. Measures taken to increase lactate clearance rate are necessary to reduce potential delirium or mortality risk in clinical.However, more evidences from prospective studies are needed to verify these findings.